An overview of public health education in South Asia: Challenges and opportunities - Anitha, Chandanadur Thippaiah; Akter, Konok; Mahadev, Kalyankar (Frontiers in Public Health, 2022)
Over the past two decades, there has been an increased demand for Public Health Education (PHE) in South Asia. While this region has a large number of Public Health (PH) institutions, the quality of PHE has not been aligned with the core PH competencies. In this article, we present an overview of Master of Public Health (MPH) programs across South Asian countries. An extensive systematic search on various web search engines regarding PH course offerings was conducted, including specific institute and educational websites. By 2021, more than 180 institutions in South Asia provided an MPH degree. Most of these institutions/universities were found in India, Pakistan, and Bangladesh, and a few among these institutions were established as independent Schools of Public Health (SPH), separate from medical colleges, and had a multidisciplinary faculty. But, dedicated training facilities in the specialized field of public health were not found in most of these institutions. Generally, a well-defined MPH curriculum is not currently available except in India where the University Grants Commission (UGC) guideline for a model MPH curriculum has been proposed by the Ministry of Health and Family Welfare. The entry criteria for an MPH degree in India is accepting students in multidisciplinary fields, while in other South Asian countries this is primarily restricted to medical/paramedical students with a basic understanding of preventive medicine. The aim of this review was to document the current and future PHE opportunities and challenges in South Asia.